Re-evaluating the NO2 hotspot over the South African Highveld - Alexandra Lourens; Timothy Butler; Johan Beukes; Pieter van Zyl; Steffen Beirle; Thomas Wagner; Klaus-Peter Heue; Jacobus Pienaar; Gerhardus Fourie; Mark Lawrence (South African Journal of Science, 2012)
Globally, numerous pollution hotspots have been identified using satellite-based instruments. One of these hotspots is the prominent NO2 hotspot over the South African Highveld. The tropospheric NO2 column density of this area is comparable to that observed for central and northern Europe, eastern North America and south-east Asia. The most well-known pollution source in this area is a large array of coal-fired power stations. Upon closer inspection, long-term means of satellite observations also show a smaller area, approximately 100 km west of the Highveld hotspot, with a seemingly less substantial NO2 column density. This area correlates with the geographical location of the Johannesburgâ€“Pretoria conurbation or megacity, one of the 40 largest metropolitan areas in the world. Ground-based measurements indicate that NO2 concentrations in the megacity have diurnal peaks in the early morning and late afternoon, which coincide with peak traffic hours and domestic combustion. During these times, NO2 concentrations in the megacity are higher than those in the Highveld hotspot. These diurnal NO2 peaks in the megacity have generally been overlooked by satellite observations because the satellites have fixed local overpass times that do not coincide with these peak periods. Consequently, the importance of NO2 over the megacity has been underestimated. We examined the diurnal cycles of NO2 ground-based measurements for the two areas â€“ the megacity and the Highveld hotspot â€“ and compared them with the satellite-based NO2 observations. Results show that the Highveld hotspot is accompanied by a second hotspot over the megacity, which is of significance for the more than 10 million people living in this megacity.